The Mineral Industry Of Other Areas Of The Far East And South Asia - Bangladesh - E. Chin (The National Institute for Occupational Safety and Health (NIOSH), 1986)
Bangladesh, whose population probably passed 100 million by yearend, remained one of the poorest countries in the world, with a per capita gross domestic product (GDP) of $126.2 Its only economically significant mineral production was natural gas. A few other minerals or mineral-based commodities were also produced, generally for local consumption. These included cement, clays, nitrogenous fertilizers, limestone, salt, steel, and pilot plant production of ilmenite and rutile. Exploration for oil was a continuing quest, which was hindered by a lack of funding and a hesitancy on the part of foreign petroleum companies to make long-term or expensive exploration commitments. PODUCTION AND TRADE Production of natural gas continued to increase as more use was being made of the abundant gas reserves variously put at between 7 and 16 trillion cubic feet. The main consumers were nitrogenous fertilizer producers and electric powerplants, but other industries were converting to natural gas from imported coal or fuel oil wherever possible.